2018
DOI: 10.1002/jcp.27533
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced tRNA‐derived fragments, novel regulatory factor for doxorubicin resistance in triple‐negative breast cancer

Abstract: Triple‐negative breast cancer (TNBC) is an aggressive subtype of epithelial breast malignancy, and chemoresistance is the major obstacle for cancer therapy. TNBC is associated with a hypoxic phenotype, and hypoxia contributes to the chemoresistance in breast cancer. Transfer RNA‐derived fragments (tDRs) represent a new class of small noncoding RNAs that can be induced specifically by hypoxia. Here, we conducted a comparative analysis of the aberrant expression of tDRs in hypoxia‐treated TNBC cell lines through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 61 publications
2
84
0
Order By: Relevance
“…SKBR‐3 cells were cultured in Roswell Park Memorial Institute 1640 medium (Multicell), whereas MCF‐7 and HBL‐100 cells were cultured in Dulbecco's modified Eagle's medium (Gibco, UK) supplemented with 10% fetal bovine serum (Gibco), 100 U/ml penicillin and 100 μg/ml streptomycin (Multicell; Sun et al, ). Cells were cultured in an atmosphere at 37°C, where it contains 5% CO 2 and a certain humidity, and the cell medium was renewed per 48 hr (Cui et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…SKBR‐3 cells were cultured in Roswell Park Memorial Institute 1640 medium (Multicell), whereas MCF‐7 and HBL‐100 cells were cultured in Dulbecco's modified Eagle's medium (Gibco, UK) supplemented with 10% fetal bovine serum (Gibco), 100 U/ml penicillin and 100 μg/ml streptomycin (Multicell; Sun et al, ). Cells were cultured in an atmosphere at 37°C, where it contains 5% CO 2 and a certain humidity, and the cell medium was renewed per 48 hr (Cui et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis showed that tDRs were involved in the maintenance of the stem cell population and regulated the phosphorylation of STAT3 and the cellular response to interleukin-6 (IL-6), which resulted in the doxorubicin resistance of TNBC. 69 Corce M et al also found that ts-47s and ts-46s were upregulated by KRAS and PIK3CA mutations, respectively. Both mutations were considered to be related to the formation of breast cancer chemoresistance, such as the resistance to lapatinib.…”
Section: Breast Cancermentioning
confidence: 94%
“…In addition to serving as biomarkers, tDRs also participate in the process of TNBC. Cui et al 151 found that tDR‐0009 and tDR‐7336 were notably upregulated in the SUM‐1315 cell lines stimulated by hypoxia; further, bioinformatic analysis indicated that these two upregulated tDRs might be involved in the chemoresistance to doxorubicin in TNBC via mediating the activation of phosphorylation of STAT3. As for other ncRNAs, such as snoRNA and snRNA, their tumour‐associated functions have been observed in multiple cancers, 152‐154 but no exact roles have been defined in TNBC, which need to be further explored in the future.…”
Section: Other Non‐coding Rnasmentioning
confidence: 99%